MATERIAL LOKAL DAN RAMAH LINGKUNGAN: INOVASI DALAM PERANCANGAN INTERIOR DENGAN INSPIRASI BUDAYA OSING - Dini, Mazaya; Aldila Yuanditasari, (Aksen : Journal of Design and Creative Industry, 2024)
Dependence on nature should encourage people to build systems that utilize nature as a life-support system. Increased awareness of environmental and sustainability issues emphasizes the importance of environmentally friendly industrial practices. The Osing community is known for its tourism and handicrafts, including abaca fiber and bamboo weaving. This research delves deeper into the cultural customs of the Osing tribe that can be identified, utilized, and developed in interior design so as to create an interior design with local cultural wealth and sustainable use of local materials as a design foundation. Using a descriptive qualitative method, it was found that the materials and handicrafts typical of the Osing tribe can be youthfully utilized to enrich interior design with diverse aesthetic elements, but also to produce functional products that reflect the cultural identity of the Osing tribe. This research is useful in showing how the use of local materials such as abaca fiber and bamboo by the Osing people in Banyuwangi Regency can create continuity between local tradition, sustainability and creativity. As such, the results of this research support the application of sustainable materials and the integration of local cultural elements in interior design, contributing to environmental preservation and local economic development.